A Broader‐scope Analysis of the Catalytic Reduction of Nitrophenols and Azo Dyes with Noble Metal Nanoparticles. Issue 11 (3rd May 2019) - Shultz, Lorianne R.; Hu, Lin; Preradovic, Konstantin; Beazley, Melanie J.; Feng, Xiaofeng; Jurca, Titel
Abstract: In addition to the broad environmental implications associated with the removal of nitroaromatics from industrial effluent, the catalytic reduction of 4‐nitrophenol (4NP ) has emerged as a benchmark model for quantifying catalytic activity of metal nanoparticles. Here we present a series of noble metal nanoparticles immobilized on amorphous carbon (Au@C, Ag@C, Pt@C and Pd@C ). All materials show competitive catalytic activity over 4NP, amino‐substituted nitrophenols (ANPs ) and azo dyes. Overall, Pd@C exhibits superior activity that increases further when exposed to recycling protocol. Moreover, testing all materials synthesized over a broader substrate scope with added functionalities reveals inconsistencies in the prognosticating ability of the ubiquitous 4NP model reaction. By incorporating variably substituted ANPs into the substrate scope and averaging performance, the resulting rank of catalyst activity more accurately reflects activity trends when applied to other reducible functionalities, such as ‐N=N‐ groups in azo dyes. Abstract : To pNP or not to pNP ? A series of noble metal nanoparticles immobilized on amorphous carbon are reported (Au, Ag, Pt, and Pd). Screening catalytic activity for the reduction of the ubiquitous paranitrophenol, amino‐nitrophenols, and azo dyes reveals competitive activity across the board, with the Pd species being most active. More importantly, it highlights the limitations of using the benchmark paranitrophenol test as a tool for catalyst selection.